The Influence of Entrepreneurial Motivation, Entrepreneurial Learning, and the Use of Social Media on Student Entrepreneurship Interest - Mulia Sosiady; Ermansyah Ermansyah (Journal of Industrial Engineering & Management Research, 2023)
The purpose of this study was to analyze the relationship between entrepreneurship motivation and interest in entrepreneurship, entrepreneurship learning and interest in entrepreneurship, the use of social media and interest in entrepreneurship. This study uses quantitative research methods with explanatory research types. The use of quantitative methods with the type of explanatory research was carried out with the aim of knowing how much influence there is between the independent variables in the form of entrepreneurial motivation, entrepreneurial learning and the use of social media on the dependent variable, namely interest in entrepreneurship. 230 students. The sampling technique in this study used a purposive sampling technique. The research instrument used was a questionnaire and documentation. The distribution of the questionnaire was used to measure the effect of the independent variables consisting of entrepreneurial motivation, entrepreneurial learning, and the use of social media on the dependent variable, namely students' entrepreneurship. This questionnaire was distributed online via WhatsApp to each respondent. This data analysis uses structural equation modeling (SEM) with SmartPLS 3.0 software tools. The instrument used in this study had previously conducted instrument testing on 30 respondents with the overall result that the instrument used had been declared valid and reliable. The data analysis steps used in this study include validity and reliability tests, uni normality and hypothesis testing. The results of this study indicate that entrepreneurial motivation has a positive and significant effect on entrepreneurship interest, entrepreneurship learning has a positive and significant effect on entrepreneurship interest, the use of social media has a positive and significant effect on entrepreneurship interest